2005
DOI: 10.1111/j.1365-2265.2005.02370.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in acromegaly and in the normal population: prevalence and determinants

Abstract: In acromegaly, hypertension is more frequent than in the general population, involves predominantly DBP, and occurs earlier, is not related to gender, and is less frequently related to family history of hypertension and IGF-I levels. IGF-I may have a protective role for DBP in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
0
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 61 publications
9
74
0
12
Order By: Relevance
“…We considered 3 prospective studies (n=2976), 23,27,29 although regression coefficients used were derived from cross-sectional analyses within those studies, 14 cross-sectional studies (n=7798), 14,[24][25][26][29][30][31][32][33][34][35]37,42 and 3 case-control comparisons (n=930). 20,22,28 Overall, the analysis included 11 704 subjects. In these studies, information about ongoing antihypertensive therapy were not always provided, and hence the state of BP treatment was inconsistent across studies.…”
Section: Study Design and Subject Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered 3 prospective studies (n=2976), 23,27,29 although regression coefficients used were derived from cross-sectional analyses within those studies, 14 cross-sectional studies (n=7798), 14,[24][25][26][29][30][31][32][33][34][35]37,42 and 3 case-control comparisons (n=930). 20,22,28 Overall, the analysis included 11 704 subjects. In these studies, information about ongoing antihypertensive therapy were not always provided, and hence the state of BP treatment was inconsistent across studies.…”
Section: Study Design and Subject Selectionmentioning
confidence: 99%
“…1 The complexity in understanding the vascular functions of IGF-1 is underscored by conflicting reports on the association between BP and IGF-1. These findings include (1) small studies (n=5) indicating that hypertensive patients had higher IGF-1 concentrations compared with normotensives (total n=250); [15][16][17][18][19] (2) a neutral 20,21 or positive relationship 22 between BP and IGF-1 in active acromegalic patients (n=305 and 21, respectively); (3) cross-sectional studies indicating a neutral relationship between BP and IGF-1 (total n=5263); 14,[23][24][25][26][27][28][29][30][31] and (4) cross-sectional studies (total n=5771), including Framingham and our own, 32 yielding significant inverse associations between BP and IGF-1. 20,28,[32][33][34][35][36][37][38][39][40] Prospective studies (n=2590) also indicate an inverse association with systolic BP in 544 young black men after 10 years 23 and a 44% reduced risk for incident hypertension in 2046 nondiabetic women over 4 years.…”
mentioning
confidence: 99%
“…Characteristically, LVH in acromegaly occurs in the absence of arterial hypertension, but is further aggravated by it: 9,19) In this study, the presence of hypertension, DM, and OSAS was found to be related to LVMI. These comorbidities frequently coexisting with acromegaly seem to contribute to the development of both LVH and LVDD.…”
Section: Discussionmentioning
confidence: 81%
“…A prevalência de hipertensão nos pacientes com acromegalia varia entre 18% e 60% em diferentes séries, e a sua incidência é mais alta do que a da população geral. Em estudo com 200 acromegálicos, a prevalência de hipertensão arterial atingiu 46% dos pacientes (48). Entretanto, a despeito da sua importância, a hipertensão arterial no contexto da acromegalia ainda não tem bem esclarecidos os seus mecanismos fi siopatológicos.…”
Section: Hipertensão Arterialunclassified